(untitled) (The Journal of Psychology and Sociology, 2019)
A sociological analysis of everyday religious practices and religious identity of representatives of different faiths now shows the presence of a number of general trends, which at the same time can be described as internally contradictory. On the one hand, there are signs of the so-called religious revival, demonstrating the increasing role of the religious component in the system of value orientations of the individual. On the other hand, it might be talk about changing of internal content of religious practices, which are transformed under the influence of secularization processes and are no longer based on the phenomenon of faith, but on the complex of traditionalism, secular spirituality, and the attractiveness of compensatory capabilities of religious institutions. The purpоse of this articlе is to examinе the content and activity of religious activities, their respective semantic content and interpretation as indicators of the level of religiosity of various social groups. Orthodoxy in modern Kazakhstan is after Islam the sec- ond largest and the level of impact on the public consciousness denomination. The paper presents the results of an empirical study of the content of religious practices of Orthodox citizens of the city of Almaty. The content, regularity and intensity of cult activities as markers of the level of religiosity of a con- fessional group are viewed through specific elements of the Orthodox religious experience (sacraments, differences in religion of the main Christian trends, etc.). The advantages of sociological methodology thus make it possible to reveal significant differences in the interpretation of the content of religious practices on the part of subjects of religious experience.